Potential medication incompatibilities in pediatric oncology prescriptions - Telles dos Santos, Maitê; Simas da Rocha, Bruno; Wunsch Lopes, Gabriela; Kempf da Silva, Débora; Webster Negretto, Giovanna; Gregianin, Lauro José (Clinical and Biomedical Research, 2023)
Introduction: Pediatric oncology patients have a limited number of venous access routes and need a large number of drugs during hospitalization. This study evaluates potential medication incompatibilities (MI) in pediatric oncology prescriptions and identifies possible factors associated with the risk of their occurrence. Methods: This cross-sectional study evaluated prescriptions from a tertiary universitary hospital from December 2014 to December 2015. The association between variables and the risk of potential incompatibilities between drugs was determined by Student’s t-test and Pearson’s chi-square, considering p < 0.05 significant. The odds ratio was calculated considering a 95% confidence interval for each drug. Results: 385 prescriptions were evaluated. The mean age of 124 patients was 9.22 years old (SD = ± 5.10), and 50.65% were male. The most frequent diagnosis and reason for hospitalization were leukemia (27.30%) and chemotherapy (36.10%). The totally implantable catheter was the most commonly used venous access (61.30%). In 87.5% of prescriptions, there was the possibility of MI, and 2108 incompatibilities were found, considering 300 different combinations between two drugs. Age, diagnosis, reason for hospitalization, and type of venous access were risk factors for potential incompatibilities (p < 0.05). The following drugs present higher risk of potential incompatibilities: leucovorin, sodium bicarbonate, cefepime, diphenhydramine, dimenhydrinate, hydrocortisone, and ondansetron, with a significant odds ratio. Conclusion: The possibility of MI in prescriptions for pediatric oncology patients is frequent. Thus, the identification of risk factors may contribute to patient safety and to the rational use of drugs.